2015
DOI: 10.1186/s13014-015-0413-9
|View full text |Cite
|
Sign up to set email alerts
|

Conservative management of a perianal rhabdomyosarcoma in a 2-year old child by Papillon’s technique

Abstract: Rhabdomyosarcoma (RMS) is the most common sarcoma in paediatric patients. A perianal site is unusual and is associated with a low cure rate. The few cases of reported perianal RMS have been associated with sequelae. Here, we report the case of a 29-month-old male child who received sequential treatment by surgery, chemotherapy and radiotherapy inspired by Papillon’s irradiation of adult anal/low-rectum cancers (including external beam radiotherapy in the gynecological exam position followed by brachytherapy) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Anus saving surgery was considered in all patients. Brachytherapy was considered but abandoned because all three still had a substantial infiltrating residual tumor and because experience from brachytherapy in PRMS in children was sparse [6,7]. The decision for abdominoperineal excision and permanent colostomy was eventually made in agreement with all three patients and their caregivers as it was felt that anus saving surgery would carry also a high risk of tumor recurrence and anal incontinence.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Anus saving surgery was considered in all patients. Brachytherapy was considered but abandoned because all three still had a substantial infiltrating residual tumor and because experience from brachytherapy in PRMS in children was sparse [6,7]. The decision for abdominoperineal excision and permanent colostomy was eventually made in agreement with all three patients and their caregivers as it was felt that anus saving surgery would carry also a high risk of tumor recurrence and anal incontinence.…”
Section: Resultsmentioning
confidence: 99%
“…Conservative surgery with brachytherapy or with proton beam radiation has also been used in perineal and PRMS but due to the rarity of the disease the number of reported cases is low. Fuchs et al (2016) [6] reported two patients and Demoor-Goldschmidt et al (2015) [7] one patient with PRMS treated with combined surgery and brachytherapy. The experience with the proton beam therapy is also limited to a few patients [16,17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Primary perineal and perianal RMS (PRMS) comprise only 2% of all RMS. 3,4 PRMS are often misdiagnosed as gluteal or perirectal abscess causing a delay in the diagnosis resulting in locoregional or distant metastasis at presentation. The importance of delayed diagnosis leading to unfavorable outcomes in PRMS patients has been emphasized by many authors.…”
Section: Pediatric Perianal Rhabdomyosarcoma: Multimodal Therapy For ...mentioning
confidence: 99%